Kepastian Hukum Peraturan Menteri Keuangan Nomor 80 Tahun 2012 - Nor Hasan (CV Rewang Rencang, 2025)
The amendment to the VAT Law through the HPP Law provides a very fundamental change, one of which is related to the VAT aspect of public transportation services which were initially included in the category of Taxable Services that are not subject to VAT, changing to Taxable Services that are exempt from VAT. This makes the Regulation of the Minister of Finance Number 80 of 2012, have no legal certainty and must be set aside because it is not in accordance with the legal principles of the formation of laws and regulations.